The Spread of Buddhism Among Western Mongolian Tribes Between the 13th and 18th Centuries Tibetan Buddhism in the Politics and Ideology of the Oirat People. - Kitinov, Baatr (Lewiston : Edwin Mellen Press, 2010)
Unlike the majority of Mongolian scholarship, this work examines the history of Buddhism among Mongolian ethnic groups. Numerous works exist on the Oirats and their history, but most of the research has been devoted to the study of Buddhism in the Mongolian empire during its formative years.
Description based upon print version of record.
Description based on print version record.
Keywords: Buddhism -- Asia, Central -- History; Buddhism -- East Asia -- History; Buddhism; Buddhism -- Asia, Central -- History; Buddhism -- East Asia -- History; Buddhism; RELIGION / Buddhism / History; RELIGION / Buddhism / Tibetan; Electronic books